An examination of racial/ethnic disparities in children's oral health in the United States. (13th September 2012) - Fisher‐Owens, Susan A.; Isong, Inyang A.; Soobader, Mah‐J; Gansky, Stuart A.; Weintraub, Jane A.; Platt, Larry J.; Newacheck, Paul W.
Abstract Objective: To assess the extent factors other than race/ethnicity explain apparent racial/ethnic disparities in children's oral health and oral health care. Methods: Data were from the 2007 National Survey of Children's Health, for children 2‐17 years (n = 82, 020). Outcomes included parental reports of child's oral health status, receiving preventive dental care, and delayed dental care/unmet need. Model‐based survey‐data‐analysis examined racial/ethnic disparities, controlling for child, family, and community/state (contextual) factors. Results: Unadjusted results show large racial/ethnic oral health disparities. Compared with non‐Hispanic White people, Hispanic and non‐Hispanic‐Black people were markedly more likely to be reported in only fair/poor oral health [odds ratios (ORs) (95% confidence intervals) 4.3 (4.0‐4.6), 2.2 (2.0‐2.4), respectively], lack preventive care [ORs 1.9 (1.8‐2.0), 1.4 (1.3‐1.5)], and experience delayed care/unmet need [ORs 1.5 (1.3‐1.7), 1.4 (1.3‐1.5)]. Adjusting for child, family, and community/state factors reduced racial/ethnic disparities. Adjusted ORs (AORs) for Hispanics and non‐Hispanic Blacks attenuated for fair/poor oral health, to 1.6 (1.5‐1.8) and 1.2 (1.1‐1.4), respectively. Adjustment eliminated disparities for lacking preventive care [AORs 1.0 (0.9‐1.1), 1.1 (1.1‐1.2)] and in Hispanics for delayed care/unmet need (AOR 1.0). Among non‐Hispanic Blacks, adjustment reversed the disparity for delayed care/unmet need [AOR 0.6 (0.6‐0.7)]. Conclusions: Racial/ethnic disparities in children's oral health status and access were attributable largely to socioeconomic and health insurance factors. Efforts to decrease disparities may be more efficacious if targeted at social, economic, and other factors associated with minority racial/ethnic status and may have positive effects on all who share similar social, economic, and cultural characteristics.